Corporate, Social Responsibility (CSR) in Nigeria: Investigating Discrepancy between Practices and Blind Spots - Hassan, Abubakar Isah; Dr. Nurhidayah Abdullah; Prof. Norma Mansor (International Journal of Business and Social Science Research, 2024)
Corporate social responsibility (CSR) has been recognized as a significant contributor to the economy of developing countries. The study uncovers the potential causes of CSR discrepancies in Nigeria, a nation with divergent business prospects, evaluates their implications, and provides effective way-outs. CSR has achieved substantial interest worldwide as enterprises attempt to weigh profit-making services with social and environmental obligations. Yet, there is extensive interest in disagreements between organizations’ CSR obligations and their actual implementation. By synthesizing documented literature, the study reveals factors responsible for the discrepancy of CSR in Nigeria, such as ineffective stakeholder involvement, consumer attitude, inadequate resources, poor frameworks, and lack of consistent reporting. Furthermore, the implications imposed by CSR are examined, including missed chances for social impact, reputational damage, consumer perception, and workers' morale and commitment. Since CSR discrepancies are crucial to both enterprises and legislators, the study underscores addressing stakeholder engagement, clear frameworks for CSR implementation, transparency in reporting, and adequate resource allocation that can bring about sustainable development. The insights provided by this study can inform CSR policy development and effective corporate practices in Nigeria.